Image-guided core needle biopsy in the diagnosis of malignant lymphoma. Issue 7 (July 2015) - Skelton, E.; Jewison, A.; Okpaluba, C.; Sallomi, J.; Lowe, J.; Ramesar, K.; Grace, R.; Howlett, D.C.
Abstract Objective Current European Society for Medical Oncology (ESMO) guidelines recommend that when feasible, surgical excision biopsy (SEB) is the ideal for diagnosis, sub-typing and grading of malignant lymphoma. We undertook this retrospective study to assess the diagnostic accuracy of image-guided core needle biopsy (CNB) in the diagnosis of malignant lymphoma, to identify the proportion of cases from which oncological treatment was subsequently instigated from the CNB diagnosis, and to evaluate the potential role for minimally invasive CNB techniques in the diagnostic pathway of malignant lymphoma. Methods All cases of lymphoma amenable to CNB between 2008 and 2013 were included. Patient records were reviewed to identify the biopsy diagnostic pathway undertaken (fine needle aspiration cytology, CNB, surgical excision biopsy). CNB specimens were graded as fully diagnostic (tumour sub-typing/grading and treatment initiated), partially diagnostic (diagnosis of lymphoma but more tissue required for sub-typing/grading), equivocal or inadequate. The effects of anatomical location, needle gauge, number of core specimens and sub-type of disease on the diagnostic yield of the sample were analysed. Results 262 patients and 323 biopsy specimens were included in the study. 237 patients underwent CNB as the initial diagnostic intervention. In 230/237 CNB was fully diagnostic (97%), allowing initiation of treatment. In 7 patients, SEB was necessary in addition to CNB to provide additional diagnostic information to allow initiation of treatment. In 72 patients, SEB was the only diagnostic test performed. Conclusion Our study showed that in 97% of suitable cases, CNB provided sufficient diagnostic information to allow treatment of malignant lymphoma to be instigated. This minimally-invasive technique is well tolerated and has advantages over surgical techniques, including reduced costs, post-procedural complications and delays on the diagnostic pathway. CNB may obviate the use of surgical techniques in the majority of suitable cases, however its success is dependent on close collaboration and acceptance by clinicians and pathologists.